Identification of an anthropometric surrogate to low birth weight in newborns: a hospital based cross sectional study - Neeluri, Rajesh; Pamarthi, Kiran (International Journal Of Community Medicine And Public Health, 2018)
Background: Low birth weight babies have less chances of survival during first year of life.Appropriate and timely care of a newborn especially if he is born with low birth weight is important but this is difficult in developing countries. There is a need to develop simple, inexpensive and practical methods to identify low birth weight newborns soon after birth. Methods: A hospital based Cross sectional study was carried out on 965 live born neonates who were born during one year period. All the anthropometric measurements are taken within 24 hours of birth. Pearson’s correlation was done to assess correlation of various anthropometric parameters with birth weight. Results: Out of 965 live born neonates, 510 (52.8%) were male babies and 455 (47.2%) were female babies. 289 (29.9%) babies had birth weight less than 2500 gms. The highest correlation among all measurements was observed between birth weight and mid arm circumference while the least correlation was between birth weight and crown heel length. AUC value for ROC curves is highest for Mid arm circumference (0.917) which shows that it is a better surrogate predictor of low birth weight (<2500 gms) in our study as compared to other anthropometric parameters. Conclusions: Measurement of mid arm circumference is easier, convenient and statistically superior to other anthropometrical parameters in detection of low birth weight newborn babies.